The assessment of soil biological activity and physico-chemical parameters in the first stage of restoration of xerothermic grassland habitats on the dune of Łużowa Góra in the Kampinos National Park: Preliminary studies - Augustyniuk-Kram, Anna; Kram, Karol J.; Ilieva-Makulec, Krassimira (Studia Ecologiae et Bioethicae, 2019)
The study was conducted on the northern arm of the inland dune Łużowa Góra in the Kampinos National Park, where the habitats of xerothermic grasslands (of the class Koelerio glaucae-Corynephoretea canescentis) are currently restored in the area of approx. 1.4 ha. The aim of our research was to assess the basic physico-chemical parameters (pH, moisture and organic matter content) and biological activity (dehydrogenase, invertase and respiratory activity) of the sand (a layer of about 40-cm depth) used to cover the reclaimed area. The number of culturable oligotrophic and copiotrophic bacteria and fungi, as well as the number and trophic diversity of nematodes, was also determined. Six study sites were selected in the area of restored habitats and two sites in their immediate vicinity, with natural succession of vegetation. Soil samples were taken three times: once from the fresh sand immediately after its introduction (in July 2018) and then again 3 and 4 months later. Our results show that the study sites differed in terms of humidity and organic matter content, which was reflected in sand biological activity. The lowest biological activity and very low density of nematodes and bacterial was found in the fresh sand. However, only 4 months later, an increase in the rate of colonisation by microorganisms and nematodes was observed.